EXPERIMENTAL EVALUATION OF MN(II)-TRANS-1,2-DIAMINOCYCLEHEXANE-N,N,N',N'TETRAACETATE AS PARAMAGNETIC CONTRAST AGENT FOR ENHANCEMENT OF CEREBRAL MENINGEOMAS IN DOGS - V. Yu. Ussov; A. I. Bezlepkin; O. Yu. Borodin; M. L. Belyanin; V. D. Filimonov (Бюллетень сибирской медицины, 2014)
Aim of research. We have evaluated the abilities of new original paramagnetic contrast agent Mn-DCTA (0,5 mol solution of Manganese(II) complex with trans-1,2-diaminocyclohexane-N,N,N',N'-tetraacetate, registered trade mark Cyclomang) for contrast-enhanced imaging of brain meningeomas in dogs.Material and methods. Twelve animals were included, all with brain tumors reveald during out-patient veterinary examinations. In ten of twelve the diagnosis was verified later by pathomorphologic study. The cerebral MRI has been carred out as set of axial, sagittal and coronal slices as thin as three to five mm, covering all the volume of brain.The scanning parameters in T1-weighted spin-ech mode were as follows: TR = 400–500 ms, TE = 15–20 ms, the dose of injected paramagnetic was standardised as 1 mmol per 10 kg of body weight. For quantitative analysis the index of enhancement was calculated.Results. In all cases the sure enhancement with clear visualization of cerebral tumor was obtained due to highly intensive uptake of Mn-DCTA to the tumor tissue. When evaluated quantitatively the uptake of Mn-DCTA to the tumor gave the index of enhancement in T1-weighted spin-echo mode as high as IE = 1,72 ± 0,18 for the central parts of tumor and IE = 2,08 ± 0,23 for the peripheral ones, where as in control animals it was far below these values. Intravenous injection of Mn-DCTA to dogs with cerebral tumors did not induce any detectable pathologic or even physiologic effects.Conclusion. Henceforth we conclude the Mn-DCTA provides highly available methodologically simple imaging of cerebral meningeomas and can be thought out as promising paramagnetic agent for clinical magnetic resonance imaging in humans.